Bilateral Congenital Posterior Hemivertebrae and Lumbar Spinal Stenosis Treated With Posterior Spinal Fusion and Instrumentation. (October 2019) - Nazareth, Alexander; Andras, Lindsay M.; Krieger, Mark D.; Skaggs, David L.
Abstract : Posterior hemivertebrae are wedge shaped deformities that can result in progressive kyphosis. Surgical intervention at an early age may be required, however choice of surgical technique is controversial. The aim of this report was to describe a case of progressive congenital lumbar kyphosis and bilateral posterior hemivertebra with retropulsion of tissue into the spinal canal treated successfully by posterior spinal fusion and instrumentation without anterior hemivertebra resection or decompression. We report on a patient with bilateral lumbar posterior hemivertebra at L1-L2 treated with posterior spinal fusion and instrumentation at less than 1 year of age. At 10 mo of age, the patient underwent posterior spinal fusion and instrumentation with resection of L1 and L2 posterior elements. No resection of the anterior aspect of the bilateral hemivertebrae was performed. Correction of the kyphotic deformity was maintained at last radiographic follow-up at five years post-operatively and there is no evidence of spinal stenosis. Early intervention with resection of posterior elements and fusion with instrumentation for bilateral congenital lumbar hemivertebrae provided adequate deformity correction and maintenance of the spinal canal width without anterior resection. Despite his young age, instrumentation was both feasible and beneficial in maintaining alignment.